What's happening with professional performance evaluation in non-university levels? - Susana Tamayo Lorenzo (ADIDE Federación, 2014)
Research and experience have confirmed that the quality of education is correlated, significantly, with the quality of their teaching. But, is important to evaluate teacher performance?, why?, to what extent the evaluation contributes to improving the quality of education?, what are the objectives of the evaluation?, external evaluation?, internal evaluation?, what are the prospects in evaluating teacher performance?, what is the regulatory framework?, is materialized in plans and programs to improve?, what is happening with the teacher evaluation?, is it good publish the results?, what dangers involves publish of results?